Manajemen Strategi Dalam Pengembangan Bisnis Jasa Angkut Barang Di PT. Berkat Laut Indonesia Jaya - Alfin Aulia Rahman; Achmad Agus Priyono; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The competition in the expedition industry is becoming increasingly intense, necessitating businesses to formulate effective business development strategies to ensure their survival. The research aims to elucidate the impact of strategic management on the expansion of cargo transport services and conduct a SWOT analysis of the Business Development Strategy for Cargo Transport Services at PT. Berkat Laut Indonesia Jaya. The study's findings indicate that proficient strategic management at PT. Berkat Laut Indonesia Jaya aids in the progression of cargo transport services. The company can optimize marketing through customer analysis, enhance operational efficiency to meet growing demands, and reinforce existing financial and operational aspects. Within the framework of the SWOT strategy analysis, this approach empowers the company to capitalize on opportunities within the transportation industry and mitigate challenges such as market competition and price fluctuations. As a result, PT. Berkat Laut Indonesia Jaya can achieve sustainable growth in the cargo transport business along sea routes, focusing on a strategic amalgamation of internal and external factors. Keywords: Management, Business Development Strategy, Cargo Transport Services